The Role of Solvent Mixture, Acetic Acid and Water in the Formation of CA Membrane for CO2/N2 Separation - Jawad, Zeinab; Ahmad, A.; Low, S.; Lee, R.; Tan, P. (Elsevier BV, 2016)
The improvement of Carbon dioxide (CO2) separation efficiency from flue gases to reduce the total energy cost of sequestration technologies in coal-fired power plants has been identified as a high-priority research area. In the past three decades, membranes have attracted the attention of chemists and engineers due to their unique separation principles (i.e., selective transport and efficient separation compared to other unit operations). In this study, the formation of cellulose acetate (CA) membrane for CO2/nitrogen (N2) separation was investigated by wet phase inversion. In order to modify the CA membrane structure, different concentration ratio of solvent mixture (acetic acid:water), acetic acid and water were studied. The CA membranes were analyzed by Fourier transform infrared spectroscopy (FTIR). The separation results supported by the characterization, where the best formulate membrane with solvent mixture ratio of 70:30 (acetic acid:water), acetic acid concentration of 63 wt% and water concentration of 27 wt% had high CO2 permeance of 400.92 GPU and slightly better CO2/N2 separation performance at 32.92 as compared to others literature.